MANFAAT HASIL BELAJAR MANAJEMEN BISNIS BUSANA BUTIK SEBAGAI KESIAPAN PERINTISAN BISNIS DISTRO BUSANA MUSLIMAH - Ariyanjani Elga Pratiwi; Cucu Ruhidawati (Universitas Pendidikan Indonesia, 2017)
The This research is about the benefit of studying results management of the business boutique fashion as pioneering readiness of the business muslim women distro. The aim of this research of being to receive the data about the benefit of studying results management of the business boutique fashion was considered from competence and the aim of the business boutique fashion of the concept command, the etiquette of business fashion, the strategy of business boutique fashion, the management of human resources of business fashion, and the management production and marketing of the business boutique fashion. The method that was used in this research that is the descriptive method with the collector's implement of the data took the form of the poll. The sample of research used the purposive sample, that is the student of boutique concentration in Studi Program of fashion design Education Faculty of the Technology and Vocational Education, the generation of 2011 and 2011 that was total 34 people. Results of this research showed that more than half of students stated results of studying the management business of boutique fashion as being inspected from business boutique fashion of the concept command, the etiquette of business fashion, the strategy of business boutique fashion, the management of human resources of business fashion, and the management production and marketing of the business boutique fashion. Resume of this research showed that more than half of students experienced the benefit of studying results management of the business boutique fashion as pioneering readiness of the business muslim women distro